Addressing curriculum deficiencies in veterinary public health: a comparison of other health professions’ experiences - Akers, Jennifer (Kansas State University, 2009)
The history of veterinary medicine is intimately intertwined with duties to public health. This has remained true over centuries, and is becoming even more important with recent significant threats to public health. Despite this, the veterinary profession is failing to meet increasing needs for veterinarians trained in population medicine and public health, nationally and internationally. Current accreditation requirements for veterinary schools and colleges are vague with regard to public health education, leaving each college or school of veterinary medicine to implement its own perception of veterinary public health education. Is the public health education in veterinary curricula adequate among U.S. veterinary colleges and schools? Our inventory of the veterinary curricula in the 28 U.S. veterinary schools and colleges revealed inadequacies in veterinary public health education delivery. We found that most colleges and schools are lacking in the major veterinary public health subjects as recommended by the American College of Veterinary Preventive Medicine and the World Health Organization. The issue of inadequacies, even deficiencies, within health professional curricula is not unique to the veterinary profession. What have other health professions proposed to correct their own perceived deficiencies within their educational curricula? We identified deficiencies and proposed solutions from three health professions and discussed their solutions as potential approaches to remedy the inconsistency in public health delivery in veterinary curricula. The dental profession addressed lack of faculty effectiveness with faculty development programs. The medical profession identified an outdated and irrelevant pre-medical curriculum and is currently considering reforming it. The chiropractic profession identified a lack of public health education in its curriculum and organized a standardized public health course. Health professions are similar in content of curricula and length of professional program. In addition, the health professions have similar pre-requisites. They also share similar challenges: faculty shortages, high student debt loads, and rising educational costs. Because of these similarities, solutions to perceived curricular deficiencies proposed in one health profession can be used to address deficiencies in other health professions. Therefore, the dental, medical, and chiropractic professions have proposed solutions that should be considered in addressing the veterinary profession's curricular deficiency of inadequacy in public health education.
Keywords: veterinary public health curricula; public health education; Biology, Veterinary Science (0778); Health Sciences, Public Health (0573)